pHLIP-modified magnetic nanoparticles for targeting acidic diseased tissue; RSC Advances; Vol. 6, iss. 65 - Demin A. M. Aleksandr Mikhaylovich; Pershina A. G. Aleksandra Gennadievna; Nevskaya K. V. Ksenia Vladimirovna; Efimova L. V. Lina Viktorovna; Shchegoleva N. N. Nina Nikiforovna; Uymin A. M. Alexandr Michaylovitch; Kuznetsov D. K. Dmitrii Konstantinovich; Shur V. Ya. Vladimir Yakovlevich; Krasnov V. P. Viktor Pavlovich; Ogorodova L. M. Lyudmila Mikhaylovna (2016, 2016)
Title screen